2018
DOI: 10.1021/acs.iecr.7b03760
|View full text |Cite
|
Sign up to set email alerts
|

Higher Alcohols Synthesis over Carbon Nanohorn-Supported KCoRhMo Catalyst: Pelletization and Kinetic Modeling

Abstract: In this study, two catalyst grain sizes (fine powders and pellets) have been investigated to elucidate the effects of both external and internal mass transfer diffusion as well as particle size during the CO hydrogenation reaction to produce higher alcohols. Catalyst grain sizes of 88 and 254 μm were advisedly chosen based on our previous investigations with a similar catalyst matrix for the higher alcohol synthesis (HAS) reaction. The focus in this work was to explore the attractive textural properties of CNH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…It should be mentioned that the water concentration was about 10% of the overall liquid products, which is negligible. For kinetic model development, a power‐law approach was applied 19,27,30–32 . Reaction rates of the individual compounds are expressed as follows: rCnormalH3OH=kCnormalH3OHpCOnormalapnormalH2normalb rCnormalH4=kCnormalH4pnormalCH3normalOHnormalcpnormalH2normald rnormalC2normalH5OH=knormalC2normalH5OHpnormalCH3normalOHnormalepCOnormalfpnormalH2normalg rnormalC3normalH7OH=knormalC3normalH7OHpC2H5normalOHnormalhpCOnormalipnormalH2normalj rnormalC4normalH9OH=knormalC4normalH9OH…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be mentioned that the water concentration was about 10% of the overall liquid products, which is negligible. For kinetic model development, a power‐law approach was applied 19,27,30–32 . Reaction rates of the individual compounds are expressed as follows: rCnormalH3OH=kCnormalH3OHpCOnormalapnormalH2normalb rCnormalH4=kCnormalH4pnormalCH3normalOHnormalcpnormalH2normald rnormalC2normalH5OH=knormalC2normalH5OHpnormalCH3normalOHnormalepCOnormalfpnormalH2normalg rnormalC3normalH7OH=knormalC3normalH7OHpC2H5normalOHnormalhpCOnormalipnormalH2normalj rnormalC4normalH9OH=knormalC4normalH9OH…”
Section: Resultsmentioning
confidence: 99%
“…For kinetic model development, a power-law approach was applied. 19,27,[30][31][32] Reaction rates of the individual compounds are expressed as follows:…”
Section: Reaction Network and Kinetic Model Developmentmentioning
confidence: 99%
“…It was proposed that graphene oxide can act as an electron donor enhancing carbides formation, which in turn enhances higher alcohol synthesis. In that case the cobalt particle size was only 8.6 nm (Table 2, entry 13) [25] . Interestingly it was also confirmed that the alcohol selectivity at the same CO conversion level was directly comparative to the ratio of Co 2 C/Co determined by XRD when using catalysts with different amounts of graphene oxide (GO) in Co/GO‐OMS catalysts [29] .…”
Section: Catalyst Selectionmentioning
confidence: 79%
“…The results suggest that the effects of GHSV on external mass-transfer diffusion are negligible in our work. The effects of internal diffusion were also estimated according to the Weisz–Prater criterion ( C WP ), which was summarized in Table S7. When C WP ≪ 1, internal diffusion limitation is negligible, and if C WP ≫ 1, there are internal diffusion effects on the reaction.…”
Section: Resultsmentioning
confidence: 99%